Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Using the fact that $AC^T = (\det A)I$ where $A$ is some arbitrary matrix and $C$ is the cofactor matrix for $A$, how can I prove that $\det C = (\det A)^{n-1}$

I really don't know how to progress on this. Tried doing some random operations on both equations to see if I can make a link somewhere and: $AC^T = \det A \implies C^T = A^{-1}\det A \implies \det C^T = (\det A)A^{-1}$

$\det C = (\det A)^{n-1} \implies \det C^T = (\det A)^{n-1}$

To be honest, I'm not even sure if the last operation I applied on the first line and the operation I applied on the second line are even legal operations.

Suggestions are welcome.

share|cite|improve this question
up vote 1 down vote accepted

$$\det(A)\det(C)=\det(A)\det(C^T)=\det(AC^T)=\det((\det A)I)=(\det A)^n$$ If $\det(A)\neq0$, then divide both sides by $\det(A)$.
If $\det(A)=0$ then it follows easily from the definition of cofactor matrix that $\det(C)=0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.